Decreased Serum 25-hydroxyvitamin D Level Causes Interventricular Septal Hypertrophy in Patients on Peritoneal Dialysis: Cardiovascular Aspects of Endogenous Vitamin D Deficiency - Bennur Esen; Irfan Sahin; Ahmet Engin Atay; Emel Saglam Gokmen; Ozlem Harmankaya Kaptanogullari; Mürvet Yılmaz; Suat Hayri Kucuk; Serdar Kahvecioglu; Nurhan Seyahi (International Journal of Nephrology)
Introduction. In the present study, we aimed to analyze the relation of vitamin D with echocardiographic indexes in patients with end stage renal disease (ESRD) receiving renal replacement therapy (RRT). Methods. A total of 98 patients, 64 patients on hemodialysis (HD) (29F/35M, mean age 56.75 ± 18.63 years) and 34 age matched patients on peritoneal dialysis (PD) (21F/13M, mean age 58.11 ± 10.63 years), with similar duration of ESRD and RRT were enrolled into this cross-sectional study. Echocardiographic examination was performed after dialysis session at normovolemic status. Fasting blood samples were obtained before dialysis session. Results. Patients on PD and female patients in both groups had significantly lower level of 25-OH-D3 level when compared to patients on HD or male patients (p: 0.0001 and p: 0.0001). When all participants were considered, there was no significant association between 25-OH-D3 and echocardiographic parameters; however, in patients on PD, a significant negative correlation was determined between 25-OH-D3 and diastolic blood pressure, interventricular septal hypertrophy (ISH), and left ventricular mass index (LVMI) (r: −0.424, p: 0.012; r: −0.508, p: 0.004; r: 0.489, p: 0.04, resp.). Conclusion. Low serum 25-hydroxyvitamin D levels is associated with ISH and LVMI in PD patients.